2019
DOI: 10.4274/turkderm.galenos.2018.34966
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the use of complementary and alternative therapy in patients with psoriasis and acne vulgaris

Abstract: Background and Design: The aim of this study was to explore the use of complementary and alternative medicine (CAM) therapy in patients with acne vulgaris (AV) and psoriasis and their attitudes towards CAM. Materials and Methods: A total of 300 patients, including 150 patients with AV and 150 patients with psoriasis, were included in the study. The patients were randomly selected among the patients who were admitted to dermatology outpatient clinic. A face-to-face structured questionnaire about CAM was applied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(11 citation statements)
references
References 18 publications
0
10
1
Order By: Relevance
“…[ 11 ] In these studies, the rate of CAM use in patients with AV is reported in a very wide range from 14.8% to 71.3%. [ 8 13 ] To our knowledge, there is only one study in the literature investigating CAM use specifically in patients with AV. [ 14 ] In that study, of the 657 patients with AV, 77% were reported to have a history of CAM use, which is similar to our finding [74.41%].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…[ 11 ] In these studies, the rate of CAM use in patients with AV is reported in a very wide range from 14.8% to 71.3%. [ 8 13 ] To our knowledge, there is only one study in the literature investigating CAM use specifically in patients with AV. [ 14 ] In that study, of the 657 patients with AV, 77% were reported to have a history of CAM use, which is similar to our finding [74.41%].…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, some publications reported a high rate of CAM use in women, whereas others did not find a relationship between CAM use and gender. [ 6 13 14 15 ] In a study conducted in Korea, 90% of the AV patients referred to CAM when their lesions increased and their disease worsened. [ 16 ] This is similar to our results concerning the higher use of CAM among the patients with more severe acne and those with higher CADI scores.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations